Implementasi Program Pelayanan Administrasi Terpadu Desa dan Kelurahan (PADU-DESK) Dalam Rangka Penyelenggaraan Pelayanan Publik di Kabupaten Kutai Kartanegara - Fathul Alamin (Jurnal Ilmu Pemerintahan Suara Khatulistiwa, 2023)
Public satisfaction with public services is an indicator to assess the achievement of the objectives of public administration. Kutai Kartanegara Regency as an area with a very large area has challenges in public services. To bring services closer and improve the quality of service to the community, the Kutai Kartanegara Regency Government created the Village and Village Integrated Administration Service (PADU-DESK) program. This research uses qualitative methods with descriptive analysis and data collection through in-depth interviews aimed at analyzing the implementation of the PADU-DESK program in Kutai Kartanegara Regency. The results of the study found that this program has not run effectively, theoretically, the factors that affect the implementation of Perbup No. 64 of 2017 from the aspects of communication, resources, bureaucratic structure, and budget factors are some of the problems that occur in the implementation of PADU-DESK. In the process of reviewing the theory, researchers found additional factors in assessing the success rate of implementing a policy, namely the level of maturity of the policy and the acceptability factor of the target group of policies, as a complement to other factors that have been proposed by George C. Edward III (1980).